Myelin repair is fostered by the corticosteroid medrysone specifically acting on astroglial subpopulations - Markley Silva Oliveira Junior; Jessica Schira-Heinen; Laura Reiche; Seulki Han; Vanessa Cristina Meira de Amorim; Isabel Lewen; Joel Gruchot; Peter Göttle; Rainer Akkermann; Kasum Azim; Patrick Küry (EBioMedicine, 2022)
Summary: Background: Multiple sclerosis is characterised by inflammation, oligodendrocyte loss and axonal demyelination and shows an additional impact on astrocytes, and their polarization. Although a certain degree of spontaneous myelin repair can be observed, disease progression, and aging impair regeneration efforts highlighting the need to better understand glial cell dynamics to establish specific regenerative treatments. Methods: Applying a chronic demyelination model, we here analysed demyelination and remyelination related effects on astrocytes and stem cell niches and studied the consequences of medrysone application on myelin repair, and astrocyte polarization. Findings: Medrysone induced recovery of mature oligodendrocytes, myelin expression and node formation. In addition, C3d/S100a10 co-expression in astrocytes was enhanced. Moreover, Timp1 expression in C3d positive astrocytes revealed another astrocytic phenotype with a myelination promoting character. Interpretation: Based on these findings, specific astrocyte subpopulations are suggested to act in a myelin regenerative way and manner the regulation of which can be positively modulated by this corticosteroid. Funding: This work was supported by the Jürgen Manchot Stiftung, the Research Commission of the medical faculty of the Heinrich-Heine-University of Düsseldorf, the Christiane and Claudia Hempel Foundation for clinical stem cell research and the James and Elisabeth Cloppenburg, Peek and Cloppenburg Düsseldorf Stiftung.